The influence of integrative motivation in learning Malay language vocabulary among foreign speakers at UNITEN / Noor Azam Abdul Rahman and Noraziah Mohd Amin - Abdul Rahman, Noor Azam; Mohd Amin, Noraziah (Academy of Language Studies, 2019)
Ellis (1994) dividesmotivation into four types, namely instrumental motivation,integrative motivation, resultative motivation and intrinsic motivation. This study discussesthe effectsof integrative motivation on foreign speakers while studying Malay Language vocabulary. The main objective of the study was to identify the influenceof integrative motivation onmale and female students while studying Malay Language vocabulary in Universiti Tenaga Nasional (UNITEN). This study was conducted in order to seek theanswer to the question of whether there was a significant difference in the influence of integrative motivation between male and female students. A questionnaire containing 10 items in the form of self-reporting statements concerning integrative motivation was used as aninstrumentof the study. The data from the questionnairesadministeredwere analysedusing SPSS software version 23 for descriptive data and inferences such as mean scoresand percentages, and the results of the ANOVA testwas analysedtoo. The results showed that there was a significant difference in the influence of integrative motivation between male and female students while studying Malay Language vocabulary, where the significant value was less than 0.05 (p <0.05). The findings showed that the majority of the male students were influenced by integrative motivation while studying Malay Language vocabulary in UNITEN compared to the female students.